Persepsi Karyawan Hotel Tentang Hiv/Aids Di Kota Denpasar Tahun 2012 - Ksamawan, Adi (Community Health)
The number of cumulative AIDS cases from 1987 to June 2012 in Indonesia, based on the type of work dominated by three groups, that is self-employed, housewives, and employees. The government is very concerned with issues of HIV / AIDS on labor so that the theme which was appointed to commemorate World AIDS Day 2011 is devoted to the protection of industrial and workers from HIV/AIDS. This theme is associated with a strategy for HIV/AIDS globally in 2011-2015 is “Getting to Zero”, which one of his vision is zero discrimination. These efforts are expected to reduce the negative stigma and discrimination against People Life With HIV/AIDS (PLWHA) in particular to workers. The purpose of this study was to get an overview of the perception of hotel employees in Denpasar about HIV/AIDS. This research is a quantitative explanatory using cross-sectional approach. The sample was 115 people were taken to the multi-stage random sampling technique. Data were collected using a questionnaire and then analyzed descriptively. The results showed that more than half of respondents had a low level of knowledge about HIV/AIDS and the level of knowledge from respondents there is no a significant difference viewed from the education, age and income. The perception of the respondents about HIV/AIDS almost equal between the “negative perception” and “positive perception” however, “negative perception” tend to be large than the “positive perception”.